Metal foil with release film, method for producing same, and method for producing electromagnetic wave shielding film
The vacuum steaming method forms a metal foil with a decapatic membrane and forms a protective film and adhesive layer on its surface. Drise and high air transparency electromagnetic wave shielding membrane.
Patent Information
- Application Number
- CN202380034885.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-04-07
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, when manufacturing low resistance metal foil and electromagnetic wave shielding film, it is difficult to evenly disperse easily soluble components, resulting in uneven film resistance, and the inclined evaporation method has problems such as complicated processes and easy destruction of the resin layer.
The crystal morphology is controlled by the vacuum evaporation method to form a metal foil with a release film, with a surface resistance of less than 0.04Ω/□, and a protective film and adhesive layer are formed on the surface of the metal foil to ensure the stability and stability of the film. Breathability.
Achieving the stable supply of metal foil with a release film that has low resistance and can transmit volatile components, improving the performance of the electromagnetic wave shielding film and the high-temperature reflow soldering passability.
Smart Images

Figure CN119365336A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a metal foil with a release film, a method for producing the same, and a method for producing an electromagnetic wave shielding film. Background Art
[0002] In recent years, smartphones and tablet-type information terminals are required to have the ability to transmit large amounts of data at high speed. In order to transmit large amounts of data at high speed, it is necessary to use high-frequency signals.
[0003] However, when using high-frequency signals, electromagnetic noise is generated by the signal circuit provided in the printed wiring board, which is likely to cause malfunction of peripheral devices. Therefore, in order to prevent such malfunction, it is important to shield the printed wiring board from the influence of electromagnetic waves.
[0004] As a method of shielding a printed wiring board, an electromagnetic wave shielding film having a shielding layer and a conductive adhesive layer is used.
[0005] For these electromagnetic wave shielding films, a conductive adhesive layer is overlapped with an opening provided on an insulating layer for covering a ground circuit of a printed wiring board, and heated and pressed, and a conductive adhesive is filled in the opening. Thus, the shielding layer and the ground circuit of the printed wiring board are connected via the conductive adhesive, thereby shielding the printed wiring board. Afterwards, in order to connect the printed wiring board to electronic components, the shielded printed wiring board is exposed to a high temperature of about 270°C in a reflow process.
[0006] In addition, after attaching the electronic component to the printed wiring board, in order to make a slight correction to the position of the electronic component, a so-called repair operation is sometimes performed, that is, the printed wiring board is heated, the electronic component is peeled off from the printed wiring board, and then attached again. Then, after the repair operation, the electronic component needs to be attached to the printed wiring board, so the electromagnetic wave shielding film is exposed to high temperature again in the reflow process (Patent Document 1).
[0007] On the other hand, with the high frequency of the transmitted signal, the shielding cover needs grounding stability in order to reduce the noise to the signal line, and low resistance is required. When a metal film is used for the shielding cover, it is necessary to use a low-resistance metal (gold, silver, copper, etc.) and make the film thicker. At this time, gas is generated from the adhesive layer of the electromagnetic wave shielding film, the insulating film of the printed wiring board, etc., and the gas is blocked by the metal film, which causes problems. In particular, when the base film of the printed wiring board is formed by a highly hygroscopic resin such as polyimide, water vapor is generated from the base film by heating. The above-mentioned volatile components generated from the adhesive layer, the insulating film, and the base film cannot pass through the metal film, so they will accumulate between the metal film and the adhesive layer. Therefore, if rapid heating is performed in the reflow process, there is a possibility that the interlayer adhesion between the metal film and the adhesive layer will be destroyed due to the volatile components accumulated between the metal film and the adhesive layer. As methods for preventing this undesirable situation, a method of forming multiple openings on a metal film to allow volatile components to pass through (Patent Document 2) and a method of using an inclined evaporation method to directly form a metal film that can pass volatile components on an electromagnetic wave shielding film (Patent Document 3) have been proposed.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2017 / 111158
[0011] Patent Document 2: Japanese Patent No. 6219383
[0012] Patent Document 3: International Publication No. 2020 / 203109 Summary of the invention
[0013] Problems to be solved by the invention
[0014] For a metal film forming an opening as in Patent Document 2, since a soluble component with high solubility in an etching solution (solvent) is dispersed in the metal film, if the shape and size of the soluble component are not uniform and uniformly dispersed, the film resistance of the metal film after the opening is formed becomes uneven, and there is a risk of causing signal noise. In addition, since the etching rate of the etching solution changes according to the frequency of use, in order to form a stable opening, it is necessary to manage the etching solution, resulting in the same difficulty and cost as the etching process for forming wiring. In particular, in the embodiment of the document, a pre-treatment process for etching rolled copper foil and electrolytic copper foil uniformly and thinly is also included, but in order to etch uniformly and thinly, the management of special equipment and special etching solution will be very strict, and the cost will be higher.
[0015] On the other hand, when the oblique evaporation method is used as in Patent Document 3, the surface of the substrate to be evaporated needs to be greatly roughened. The thickness of the protective film used in electromagnetic wave shielding and the resin layer and film used are as thin as about 5μm to 10μm, and there is a problem of difficulty in the process when roughening them. If a sandblasting method suitable for generating a roughened surface suitable for oblique evaporation is used, it is also easy to penetrate the resin layer and film and fail to protect the metal film.
[0016] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to stably provide a metal foil with a release film which has a low electrical resistance and is permeable to volatile components, and an electromagnetic wave shielding film using the same.
[0017] Means for solving problems
[0018] The inventors of the present application have conducted intensive studies in view of the above-mentioned problems and have found that a metal foil with a release film which has low electrical resistance and is permeable to volatile components can be obtained by controlling the crystal morphology by a vacuum deposition method.
[0019] That is, the present invention relates to a metal foil with a release film, which is a metal foil with a release film, which comprises a release layer and a metal foil in this order on one side of the film, wherein the surface resistance of the metal foil is 0.04 Ω / □ or less, and the water vapor transmission rate of the metal foil according to JIS K7129-2:2019 is 3.5 g / (m 2 · days) or more.
[0020] The present invention is also a method for producing a metal foil with a release film, and relates to a method for producing a metal foil with a release film, wherein the metal foil is formed into a film by a vacuum deposition method.
[0021] The present invention also relates to a method for producing an electromagnetic wave shielding film, comprising forming an adhesive layer on one side of a metal foil peeled from the metal foil with a release film, and forming a protective film on the side of the metal foil opposite to the side on which the adhesive is formed.
[0022] Effects of the Invention
[0023] In the present invention, a metal foil having a controlled crystal morphology is formed by roughening the surface of a release film by vacuum deposition, thereby providing a metal foil with a release film having low resistance and capable of transmitting volatile components, and an electromagnetic wave shielding film using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] [ Figure 1 ] is a cross-sectional schematic diagram of a conventional method of producing a metal foil with a release film using a vacuum evaporation method.
[0025] [ Figure 2] is a schematic cross-sectional view of a method for producing a metal foil with a release film using an inclined evaporation method of a vacuum evaporation method.
[0026] [ Figure 3 ] is a schematic cross-sectional view of a method for producing a metal foil with a release film of the present invention using a vacuum evaporation method.
[0027] [ Figure 4 ] is a cross-sectional view of a metal foil with a release film according to an embodiment of the present invention.
[0028] [ Figure 5 ] is a cross-sectional view of the electromagnetic wave shielding film.
[0029] [ Figure 6 ] is a cross-sectional view when a protective film is formed on the metal foil with a release film involved in an embodiment of the present invention.
[0030] [ Figure 7 ] is a cross-sectional view of a case where a protective film is formed on a metal foil with a release film according to an embodiment of the present invention, and a different release film is laminated on the protective film.
[0031] [ Figure 8 ] is a cross-sectional view of a protective film formed on a metal foil with a release film according to an embodiment of the present invention, and an adhesive is applied after laminating a different release film on the protective film.
[0032] [ Fig. 9 ] is a cross-sectional view when release films are laminated on both sides of the electromagnetic wave shielding film.
[0033] [ Fig.10 ] is a cross-sectional view of a shielded printed wiring board. DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described in detail.
[0035] <Metal foil with release film>
[0036] The metal foil with a release film 1 of the present invention has a metal foil 301 ( Figure 4 ).
[0037] <Electromagnetic wave shielding film>
[0038] The electromagnetic wave shielding film 2 is obtained by peeling off the metal foil 301 from the release film 3 of the metal foil with release film, and the metal foil 301 has an adhesive layer 601 and a protective film 602 ( Figure 5 ).
[0039] <Metal Foil>
[0040] The metal foil in the present invention is an aggregate of metal layers formed by laminating one or more layers having a metal as a main component (hereinafter referred to as metal foil). The main component refers to a substance that accounts for more than 50 atomic % when the entire layer is taken as 100 atomic %.
[0041] The surface resistance of the metal foil 301 in the present invention is preferably 0.04Ω / □ or less, and more preferably 0.02Ω / □ or less. When transmitting high-frequency signals, the shielding device needs to shield the noise generated by the signal line, and grounding stability is required. If the resistance of the shielding device is high, in addition to the decrease in the shielding rate of the noise, a voltage drop caused by the resistance is also generated, and a potential is generated in the shielding device, which becomes one of the causes of transmission attenuation of the signal line. The lower the surface resistance of the metal foil, the better. For high-frequency signals above 1GHz, the surface resistance value is preferably 0.04Ω / □ or less, and more preferably 0.02Ω / □ or less. The lower the resistance value, the better, but as a lower limit, it is 10 -5 Ω / □ or so.
[0042] The main component of the metal foil in the present invention is preferably any metal selected from the group consisting of copper, silver, and aluminum. The so-called main component here refers to a substance that exceeds 35 atomic % when the entire layer is set to 100 atomic %. The reason is that, considering the shielding characteristics and signal attenuation characteristics of the metal foil, the lower the resistance, the better. Gold can also be used in terms of performance, but it is expensive in terms of cost and is sometimes not suitable for use as an electromagnetic wave shielding film. Considering the cost and resistance, the main component of the metal layer is preferably copper. From the perspective of setting the surface resistance value to less than 0.04Ω / □, the thickness of the metal foil is preferably 0.5μm or more. It should be noted that as long as the surface resistance is within the specified range, oxides, nitrides, etc. may also be included in a part. In addition, in order to prevent rust, a metal layer of nickel or titanium of more than 1nm can also be formed on the surface layer by a vapor deposition method such as sputtering. It should be noted that in the present invention, it is preferred that the main component of the metal layer is a layer of any metal selected from the group consisting of copper, silver, and aluminum. When the metal foil is formed by multiple metal layers, the main component of all the metal layers does not necessarily have to be any metal selected from the group consisting of copper, silver, and aluminum.
[0043] As for the water vapor permeability, when the metal foil is thin, it may be broken during measurement and difficult to measure, so it is measured with a release film. The water vapor permeability of the metal foil 1 with a release film according to JIS K7129-2:2019 is preferably 3.5 g / (m 2 ·day) or more, more preferably 5.0g / (m 2 Water vapor transmission rate is less than 3.5g / (m 2·day), if rapid heating is performed during the reflow process, the volatile components including water vapor will be shielded by the metal foil, and the possibility of interlayer adhesion being destroyed due to rapid vaporization of the volatile components becomes high. If the water vapor permeability of the metal foil 1 with a release film is 3.5 g / (m 2 ·day) or more, the possibility of interlayer adhesion being destroyed during reflow soldering becomes lower. If 5.0g / (m 2 The possibility of being destroyed is further reduced if the water vapor transmission rate is above 1,000 g / (m 2 · days) or so.
[0044] The water vapor permeability is 3.5g / (m 2 A method for forming a metal foil 1 with a release film of more than 10 days is preferably exemplified by a method in which a metal foil 301 is formed on a release film 3 having a release layer 501 formed on one side of the film 101 by a vacuum deposition method.
[0045] It is known that the crystal structure of a metal layer formed by a sputtering method and a metal layer formed by a vacuum evaporation method depends on the film forming temperature. In general, when the melting point of the metal is set to Tm and the film forming temperature is set to Td, when Td < 0.7Tm, the formed metal layer becomes a columnar crystal. Since the melting point of copper is 1083°C, if the film forming temperature is sufficiently lower than 0.7Tm, i.e., 758°C, the copper layer becomes a columnar crystal structure. Since it is believed that the film forming temperature of the copper layer is approximately the same as the temperature on the film, it can be confirmed that by making the copper layer a columnar crystal, the temperature on the film can be maintained sufficiently low, thereby reducing thermal damage. With respect to the crystal structure, the EBSD (Electron Backscattered Diffraction) method can be used to observe the cross-sectional area of the metal foil. It should be noted that when the metal foil is formed, if the film does not shrink or deform greatly due to heat, it will be sufficiently cooled, and the crystal structure becomes a columnar crystal structure. In the case of normal vacuum evaporation, such as Figure 1 As shown, the vapor-deposited metal is incident on the release film 3 as a substrate along the vapor deposition direction 201, and a metal foil 301 is formed on the release film 3. It is known that at this time, the crystal growth of the metal layer grows in a columnar shape along the vapor deposition film growth direction 401 relative to the release film 3, and the metal foil 301 becomes a columnar crystal. As the film thickness increases with the progress of vapor deposition, the columnar crystals grow thicker in the lateral direction, and the adjacent columnar crystals grow densely connected, thereby eliminating the gaps through which water vapor and the like can pass, and the gas barrier property becomes higher. In contrast, there is a method in which vapor deposition is performed on a film as a substrate from an oblique direction, such as Figure 2Such a method is called inclined evaporation. The characteristic of this method is that if the evaporated metal is incident along the evaporation direction 201 relative to the release film 3, the metal grows into columnar crystals in the growth direction 401 of the evaporated film, so the columnar crystals are not easy to grow laterally, and gaps are generated between the columnar crystals. If there are gaps between the columnar crystals of the metal layer, a film with good water vapor permeability at low density can be made. According to this method, even if the thickness of the metal foil is increased, the columnar crystals will not expand laterally, so there are gaps in the metal foil, and the water vapor permeability can be maintained even if the thickness of the metal foil is increased. However, in the usual inclined evaporation, since the evaporation is tilted to 60 to 80 degrees, the utilization efficiency of the material decreases, and the film forming speed of vacuum evaporation decreases significantly. In addition, since the crystal orientation is consistent and there are gaps, it also has the characteristic of being easy to become brittle in terms of mechanical properties.
[0046] The present invention is realized by focusing on the following situation: as a method for maintaining the water vapor permeability of the metal foil formed by the oblique vapor deposition without reducing the film forming speed, by forming unevenness on the surface of the release film 3 as a base material, partial oblique vapor deposition occurs in an arbitrary direction on the surface of the release film 3, and gaps can be ensured between crystals. Figure 3 As shown, the vapor-deposited metal is incident along the vapor deposition direction 201 with respect to the release film 3, which is a substrate having irregularities on the surface, to form a metal foil 301 on the release film 3. At this time, the vapor deposition direction becomes inclined relative to the film surface due to the irregularities of the release film 3, and thus becomes an inclined vapor deposition, and the metal begins to grow in a columnar manner in a direction different from the vapor deposition incident direction. Among them, since the vapor deposition incident direction becomes random in the film position, the direction of the columnar growth tends to be a random direction, and since the growth direction contacts the adjacent crystals, the columnar growth is hindered, and intermittent and short columnar growth is repeated. The lateral growth, which is a characteristic of the inclined vapor deposition, is small, and therefore gaps are generated between the columnar crystals, making it possible to produce a metal foil with excellent water vapor permeability. In addition, as in the example Figure 2 Compared with the conventional inclined evaporation shown, the crystal growth orientation is not uniform, so the film strength does not become brittle.
[0047] The arithmetic mean roughness Ra of the film surface of the release film 3 is preferably 0.4 μm or more, and the ten-point average roughness Rz is preferably 2.5 μm or more. Ra and Rz are parameters according to JIS B0601:1994. When the surface roughness Ra is 0.4 μm or more and Rz is 2.5 μm or more, the following situation exists: it is easy to show the same effect as oblique evaporation, and a metal foil with good water vapor permeability can be generated. The detailed conditions for the average roughness measurement are stated in the examples below, which are set as follows: using the high-precision fine shape measuring machine Surfcorder ET4000A manufactured by Kosaka Laboratory Co., Ltd., using a stylus with a front end R2 μm, an area of 500 μm×500 μm is measured.
[0048] The root mean square tilt RΔq of the film surface of the release film 3 is preferably 0.18 or more. In addition, the arithmetic mean tilt angle RΔa of the film surface is preferably 7.0° or more, more preferably 8.0° or more. The root mean square tilt RΔq is a parameter according to JISB0601:2001, which represents the root mean square of the local tilt dZ / dX in the reference length. The local tilt mentioned here is the value obtained by differentiating the roughness curve Z(x) representing the cross-sectional roughness, and the differentiation basically uses the 7-point formula. On the other hand, the arithmetic mean tilt angle RΔa is the absolute value of the inclination of the line segment formed by the surface concavity and convexity obtained relative to the reference length X of the roughness curve, and the value obtained by averaging it. In order to obtain the same effect as inclined evaporation through the surface concavity and convexity of the film, it is preferred that the inclination of the concavity and convexity is large, and the growth direction of the crystal is easy to become inclined. If the root mean square tilt RΔq is less than 0.18, or the arithmetic mean tilt angle RΔa is less than 7.0°, the change in the crystal growth direction caused by the concavoconvex is small, so the crystal is easy to grow in the same direction, the crystal grows greatly and becomes dense, and sometimes the water vapor permeability decreases. The details of the measurement conditions are described later in the examples, which are set as follows: using a shape measurement laser microscope VK-9710 (laser light source wavelength is 408nm) of Keyence Corporation, using a 50x objective lens for measurement, and using the average value obtained by measuring the line roughness of 200μm in length in two orthogonal directions.
[0049] It should be noted that, regarding the inclination of the film surface, it is preferred that the root mean square inclination angle obtained by measuring using the above-mentioned laser microscope is also large. The root mean square inclination angle of the roughness curve on the film surface on the side with the metal foil is preferably 10.0° or more, more preferably 12.0° or more. It should be noted that the so-called root mean square inclination angle is the square root of the square root of the value obtained by calculating the inclination of the line segment formed by the surface concavity and convexity relative to the reference length X of the roughness curve.
[0050] Since the lateral growth and height growth of columnar crystals are suppressed by local inclined evaporation based on surface roughening, thereby generating gaps between crystals, a metal foil with good water vapor permeability can be generated, so the size of the crystal grain size is important. The average crystal grain size of the metal foil 301 is preferably between 50 nm and 200 nm, and more preferably between 50 nm and 180 nm. When the average crystal grain size is less than 50 nm, the gaps between the crystals become too large, and the surface resistance of the metal foil sometimes increases compared to the appropriate range. On the other hand, if the average crystal grain size exceeds 200 nm, the gaps between the crystals become smaller, the water vapor permeability decreases, and sometimes it is impossible to ensure that the water vapor permeability of the metal foil 1 with a release film is 3.5 g / (m 2It should be noted that the average crystal grain size can be studied by using the EBSD (Electron Backscattered Diffraction) method on the cross section of the metal foil of the laminate.
[0051] The metal foil 301 of the metal foil with a release film 1 of the present invention preferably has a low electrical resistance, and therefore preferably has a larger film thickness. However, when the metal foil 301 is formed by vacuum evaporation, if the film thickness is increased, the metal foil 301 may fall off from the release film 3 during evaporation due to the stress and self-weight generated in the metal foil 301. Therefore, from the viewpoint of the process passability of vacuum evaporation, the thickness of the metal foil 301 is preferably 3.0 μm or less.
[0052] The arithmetic mean roughness Ra of the surface on the metal foil 301 side of the metal foil 1 with a release film is preferably 0.5 μm or more, and the ten-point average roughness Rz is 3.5 μm or more. The definition and measurement method of the parameters are the same as those of the above-mentioned film. When Ra is 0.5 μm or more and Rz is 3.5 μm or more, the surface roughness exhibits the same effect as oblique evaporation, and becomes a metal foil with good water vapor permeability. If Ra is less than 0.5 μm, or Rz is less than 3.5 μm, the effect of the roughness of the release film 3 is insufficient in the process of forming the metal foil, and sometimes the crystal grows significantly and the water vapor permeability decreases.
[0053] The root mean square inclination RΔq of the roughness curve on the surface of the metal foil 301 side of the metal foil 1 with a release film is preferably 0.10 or more, and the arithmetic mean inclination angle RΔa is 3.0° or more, and the arithmetic mean inclination angle RΔa is more preferably 7.0° or more. The definition and measurement method of the parameters are the same as those of the above-mentioned film. It is believed that if RΔq is 0.10 or more, or RΔa is 3.0° or more, the crystal size of the metal foil becomes smaller due to the inclination of the concave and convex of the film, and the water vapor permeability becomes higher. On the other hand, when RΔq is less than 0.10, or RΔa is less than 3.0°, the effect of the inclination of the concave and convex of the release film is small, and sometimes it does not become a crystal growth like inclined evaporation, and there is a situation where the crystal size becomes larger and the water vapor permeability decreases.
[0054] It should be noted that, similarly to the above-mentioned release film, the inclination of the metal foil surface preferably has a large root mean square inclination angle. The root mean square inclination angle of the roughness curve on the surface of the metal foil is preferably 6.0° or more, more preferably 10.0° or more.
[0055] <Film>
[0056] The so-called film 101 used in the present invention is a material formed by molding a polymer such as a synthetic resin into a thin film. The film 101 can use a polyester film such as a polyethylene terephthalate film and a polyethylene naphthalate film, a polyimide film, a polyphenylene sulfide film, a polypropylene film, and a polyetheretherketone film. Among them, a polyethylene terephthalate film is more preferably used. These films can be used alone or in combination. Since it is used as a substrate for a release film, the film thickness is preferably 15 μm to 150 μm. If the handling during vacuum evaporation and the processability of the surface unevenness are taken into consideration, it is further preferably 25 μm to 100 μm.
[0057] There is no particular limitation on the method for preparing the unevenness on the film surface, and the methods that can be used include: forming the unevenness on the film by shot peening; thinly coating a resin containing large particles such as fillers to form the unevenness with the particles; and pre-incorporating the particles when the film is formed.
[0058] Shot peening is a method of imparting fine irregularities to a film by blowing fine particles such as an abrasive material onto the film. Abrasive materials may be known materials such as ceramic beads and glass beads formed of silica sand, alumina, zirconium oxide, silicon dioxide, etc., dry ice particles, etc. The method of blowing the abrasive material is not particularly limited, and may be shot peening by blowing the abrasive material by centrifugal force (centrifugal shot peening), air shot peening using compressed air, wet shot peening by forming a slurry and performing high-pressure spraying, etc.
[0059] In the case of forming concavoconvex by coating the resin containing particles, the type of resin is not particularly limited, but in order to ensure the close contact between the film and the resin layer, it is preferred to use an organic component as the main resin. As the type of resin, for example, polyester resin, polyurethane resin, acrylic resin, methacrylic resin, polyamide resin, polyethylene resin, polypropylene resin, polyvinyl chloride resin, polyvinylidene chloride resin, polystyrene resin, polyvinyl acetate resin, etc. can be cited. These resins can be used alone, or copolymers or mixtures of more than two kinds can also be used. Among them, from the viewpoint of close contact and particle dispersibility, polyester resin, polyurethane resin, acrylic resin or methacrylic resin are preferred.
[0060] The shape of the particles used to form the concavoconvex can be, for example, star-shaped, flat, rhombus-shaped, rectangular, needle-shaped, candy-shaped, a non-spherical shape such as an indefinite shape, or a spherical shape (a shape in which the cross-sectional shape of the particle is surrounded by a curved surface), etc. In addition, the particles can be porous, non-porous, or hollow, and particles with different particle shapes can also be mixed.
[0061] The material of the particle can be any of organic compounds and inorganic compounds, and is not particularly limited. It is also possible to mix particles of different materials and use them. As the material of the particle, in the case of organic compounds, it is preferred to use a resin with a cross-linked polymer component of a high melting point as the main body, such as polyamide resin particles, polyurethane resins, acrylic resins, methacrylic resins, polyamide resins, polyethylene resins, polypropylene resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl acetate resins, fluorine resins, silicone resins, etc. such as polyester resins and benzoguanamine. These resins can be alone, or the resins made of copolymers or mixtures of more than two kinds can be used. In the case of inorganic compounds, for example, calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, silicon dioxide, aluminum oxide, mica, titanium mica, talc, clay, kaolin, lithium fluoride, calcium fluoride, etc. can be mentioned.
[0062] The thickness of the resin layer applied to form the concavoconvex is not particularly limited, but is preferably 0.05 μm to 5 μm. When the thickness is thinner than 0.05 μm, the resin layer may become uneven or particles may fall off, and when the thickness is thicker than 5 μm, the resin layer may crack or the heat resistance of the film itself may be impaired.
[0063] <Mold release layer>
[0064] The surface of the film 101 is made uneven, and a release layer 501 is formed on the produced uneven surface, thereby producing a release film 3. As for the release layer 501, it is sufficient as long as a metal foil can be formed on the release layer, and it is sufficient as long as the film 101 and the metal foil 301 can be peeled off after the metal foil 301 is formed. The release layer 501 after peeling can be attached to either the film 101 or the metal foil 301. The release layer 501 in the present invention is preferably made of melamine resin, cellulose resin, carbon layer, etc. Any release layer can be used. Melamine resin and cellulose resin are formed by coating into a film shape, while the carbon layer can be formed by sputtering or CVD, so it can be formed simultaneously with the formation of the metal foil in one device.
[0065] The method of applying melamine resin and cellulose resin as a release layer to the film can exemplify the coating method, but is not particularly limited. The coating method can use a gravure coater, a comma coater, a reverse coater, a slot die coater, etc. In the case of using melamine resin and cellulose resin as a release layer, if the thickness of the peeling layer is less than 0.1 μm, there is a possibility that the peeling layer does not fully cover the surface of the substrate, and there is a possibility that the peeling force when peeling the copper layer and the film becomes larger and cannot be peeled off. In addition, if the thickness of the peeling layer exceeds 2.0 μm, when vacuum evaporation is performed to form the copper layer, the peeling layer is vaporized, and defects such as pinholes may be generated in the metal layer. Therefore, the preferred thickness of the peeling layer is 0.1 μm or more and 2.0 μm or less.
[0066] When the carbon layer is used as a peeling layer, the formation method includes a method based on vapor deposition and a method of electrolytically depositing a carbon film from an organic solvent. Among the methods based on vapor deposition, arc ion plating, magnetron sputtering, high-frequency plasma CVD, pulsed DC plasma CVD, ionized vapor deposition plasma ion implantation film forming, etc. are exemplified. Preferably, a magnetron sputtering method that can be easily deviceized is used. In the magnetron sputtering method, argon gas and nitrogen gas are preferably used.
[0067] The thickness of the carbon layer is preferably 0.5 nm to 5.0 nm. If it is less than 0.5 nm, the adhesion strength becomes strong and cannot be peeled off. In addition, if it exceeds 5.0 nm, the peeling force between the carbon layer and the copper film becomes weak, and peeling may occur during the evaporation and transportation. More preferably, it is 1.0 nm to 4.0 nm.
[0068] The thickness of the carbon layer is difficult to measure directly, but can be calculated from the transmittance using the Lambert-Beer law described below.
[0069] [Mathematical formula 1]
[0070] I=I0e (-αZ) =I0e (-4πkZ / λ) .
[0071] Here, I0 is the amount of light before the film passes through, I is the amount of light after the film passes through, α is the absorption coefficient, Z is the film thickness, k is the attenuation coefficient, and λ is the wavelength.
[0072] <Protective film>
[0073] The protective film is not particularly limited, but preferably a resin is used, and a thermoplastic resin composition, a thermosetting resin composition, an active energy ray-curable composition, or the like can be used.
[0074] The thermoplastic resin composition is not particularly limited, and examples thereof include styrene resin compositions, vinyl acetate resin compositions, polyester resin compositions, polyethylene resin compositions, polypropylene resin compositions, imide resin compositions, or acrylic resin compositions. The thermosetting resin composition is not particularly limited, and a phenolic resin composition, an epoxy resin composition, a carbamate resin composition having an isocyanate group at the end, a urea resin having an isocyanate group at the end, a carbamate urea resin having an isocyanate group at the end, a melamine resin composition, or an alkyd resin composition may be used. In addition, there is no particular limitation on the active energy line curable composition, and for example, a polymerizable compound having at least two (meth)acryloyloxy groups in the molecule may be used. These resins may be used alone or in combination of two or more.
[0075] Among these, from the viewpoint of improving the reflow resistance and preventing the decrease of the electrical connection between the electromagnetic wave shielding film 2 and the printed wiring board, it is preferred to use a urethane urea resin having an isocyanate group at the end or a urethane urea resin having an isocyanate group at the end and an epoxy resin. The urethane resin having an isocyanate group at the end or the urethane urea resin having an isocyanate group at the end preferably has an acid value of 1 to 30 mgKOH / g, and more preferably has an acid value of 3 to 20 mgKOH / g. In addition, two or more urethane resins or urethane urea resins having an acid value in the range of 1 to 30 mgKOH / g and different acid values can also be used. When the acid value is 1 mgKOH / g or more, the reflow resistance of the electromagnetic wave shielding film becomes good, and when the acid value is 30 mgKOH / g or less, the bending resistance of the electromagnetic wave shielding film becomes good. It should be noted that the acid value is measured according to JISK0070:1992. The film 101 formed by coating a resin on a carrier film may be formed of a single material or may be formed of two or more materials.
[0076] The protective film 602 may contain at least one of a curing accelerator, a tackifier, an antioxidant, a pigment, a dye, a plasticizer, an ultraviolet absorber, a defoamer, a leveling agent, a filler, a flame retardant, a viscosity modifier, and an anti-blocking agent as needed.
[0077] The protective film 602 may be a laminate of two or more layers having different physical properties such as material, hardness, or elastic modulus. For example, if it is a laminate of an outer layer with low hardness and an inner layer with high hardness, the outer layer has a buffering effect, so that the pressure applied to the metal foil 301 can be relieved during the process of heating and pressurizing the electromagnetic wave shielding film 2 on the printed wiring board, and the damage to the metal foil 301 due to the step difference set on the printed wiring board can be suppressed, so it is preferred.
[0078] The thickness of the protective film 602 is not particularly limited and can be appropriately set as needed, preferably 1 μm to 20 μm, more preferably 1 μm to 10 μm, and further preferably 4 μm to 6 μm. If the thickness of the protective film 602 is 1 μm or more, the adhesive layer 601 and the metal foil 301 can be protected. If the thickness of the protective film 602 is 20 μm or less, the bendability of the electromagnetic wave shielding film 2 can be ensured, and it becomes easy to apply one electromagnetic wave shielding film 2 to a component requiring bendability, so it is preferred.
[0079] Therefore, the protective film 602 preferably contains at least one resin selected from the group consisting of polyester, polyimide, polyphenylene sulfide, polypropylene, polyetheretherketone, and epoxy resin. The protective film 602 needs to have excellent heat resistance in consideration of reflow soldering performance, and among these, polyimide, polyphenylene sulfide, polyetheretherketone, and epoxy resin are more preferably used.
[0080] <Adhesive layer>
[0081] The adhesive layer 601 is not particularly limited as long as it can fix the electromagnetic wave shielding film 2 to the printed wiring board, but is preferably a conductive adhesive layer having an adhesive resin composition and a conductive filler.
[0082] As the adhesive resin composition, there is no particular limitation, and can be used: thermoplastic resin compositions such as styrene resin compositions, vinyl acetate resin compositions, polyester resin compositions, polyethylene resin compositions, polypropylene resin compositions, imide resin compositions, amide resin compositions, or acrylic resin compositions, or thermosetting resin compositions such as phenolic resin compositions, epoxy resin compositions, urethane resin compositions, melamine resin compositions, or alkyd resin compositions, etc. These can be used alone or in combination of two or more.
[0083] The adhesive layer 601 may contain a curing accelerator, a tackifier, an antioxidant, a pigment, a dye, a plasticizer, an ultraviolet absorber, a defoaming agent, a leveling agent, a filler, a flame retardant, a viscosity modifier, and the like as necessary.
[0084] The thickness of the adhesive layer 601 is not particularly limited and may be appropriately set as needed, but is preferably 3 μm or more and 10 μm or less, and more preferably 4 μm or more and 7 μm or less.
[0085] The conductive filler is not particularly limited, and for example, metal fillers, metal-coated resin fillers, carbon fillers, and mixtures thereof can be used. The metal fillers include copper powder, silver powder, nickel powder, silver-coated copper powder, gold-coated copper powder, silver-coated nickel powder, and gold-coated nickel powder. These metal powders can be prepared by electrolysis, atomization, or reduction.
[0086] In particular, in order to facilitate contact between fillers, the average particle size of the conductive filler is preferably set to 3 μm or more and 50 μm or less. In addition, the shape of the conductive filler includes spherical, flake, dendritic, fibrous, etc. Among these, from the viewpoint of connection resistance and cost, at least one selected from the group consisting of silver powder, silver-coated copper powder, and copper powder is preferred.
[0087] By making the adhesive layer 601 contain a conductive filler, it can be made into an anisotropic conductive adhesive layer or an isotropic conductive adhesive layer.
[0088] Regarding the amount of conductive filler, in the case of an isotropic conductive adhesive layer, the amount may be greater than 39% by weight and less than 400% by weight relative to the total amount of the adhesive layer 601. In the case of an anisotropic conductive adhesive layer, the amount may be greater than 3% by weight and less than 39% by weight relative to the total amount of the adhesive layer 601.
[0089] <Rust-proof layer>
[0090] The surface of the metal foil 301 on the opposite side of the film 101 of the metal foil 1 with a release film of the present invention may have an anti-rust layer. By providing the anti-rust layer, it is expected to prevent the surface oxidation of the metal foil 301. As the anti-rust layer, it is preferred to form a metal anti-rust layer on the surface of the metal foil 301 on the opposite side of the film 101 of the metal foil 1 with a release film by sputtering. As far as the sputtering method is concerned, the thickness of the anti-rust layer can be made thinner, which is most suitable for the use of electromagnetic wave shielding film that further requires thin film.
[0091] As the rust-proof layer, it is preferable to use a metal layer including at least one selected from the group consisting of nickel, titanium, and chromium. When the metal foil 301 is copper and the protective film 602 is a material that diffuses copper, such as polyimide, the adhesion between the metal foil 301 and the protective film 602 cannot be ensured. In such a case, by selecting nickel, titanium, chromium, etc. that do not easily react with both the protective film 602 and the metal foil 301, the rust-proof layer can also function as a buffer layer.
[0092] The thickness of the rust-proof layer is preferably 2 nm or more and 30 nm or less, and further, more preferably 10 nm or more and 20 nm or less. If the thickness is less than 2 nm, sufficient rust-proof effect may not be obtained. On the other hand, if the thickness exceeds 40 nm, the rust-proof effect will not increase, so it is not necessary to be thicker than this. In the case where the rust-proof layer acts as a buffer layer that does not allow the protective film 602 to directly contact the metal foil 301, the thickness of the rust-proof layer is more preferably 10 nm or more, and more preferably 20 nm or less at which the rust-proof effect begins to saturate.
[0093] (Method for producing metal foil with release film)
[0094] Next, an example of a method for producing the metal foil with a release film 1 of the present invention is described. The method for producing the metal foil with a release film 1 of the present invention is not particularly limited, and for example, a method having a step of preparing the film 101, a step of forming the release layer 501 on the film 101, and a step of forming the metal foil 301 can be exemplified.
[0095] <Membranes preparation process>
[0096] The film 101 exemplified above is prepared, and the film surface on the side where the metal foil 301 is formed is roughened. The roughening method is not particularly limited, and examples thereof include a method of applying the aforementioned sandblasting to the film surface to give the film surface irregularities, and a method of applying a coating material containing particles such as the aforementioned filler to the surface to give the film irregularities.
[0097] Shot peening is a method of imparting fine irregularities to a film by blowing fine particles such as an abrasive material onto the film. Abrasive materials may be known materials such as ceramic beads and glass beads formed of silica sand, alumina, zirconium oxide, silicon dioxide, etc., dry ice particles, etc. The method of blowing the abrasive material is not particularly limited, and may be shot peening by blowing the abrasive material by centrifugal force (centrifugal shot peening), air shot peening using compressed air, wet shot peening by forming a slurry and performing high-pressure spraying, etc.
[0098] When the resin containing particles is coated to form projections and depressions, the coating method is not particularly limited, and various coating methods such as gravure coating, roll coating, die coating, spin coating, reverse coating, rod coating, web coating, blade coating, air knife coating, and dip coating can be used.
[0099] <Mold release layer forming step>
[0100] Next, as a manufacturing method for forming a release layer on the surface of the film 101, for example, the film is placed in a batch vacuum deposition apparatus (EBH-800 manufactured by ULVAC), and a carbon target having a size of 50 mm×550 mm is used, and the vacuum degree is adjusted to 5×10 -1 Pa or less, and continuously applying DC power for a time period to achieve a predetermined carbon layer thickness, thereby forming the release layer 501. It should be noted that the vacuum evaporation for forming the metal foil 301 after sputtering can be performed continuously without contact with the atmosphere between sputtering and evaporation.
[0101] <Metal foil forming process>
[0102] Next, the metal foil 301 is formed on the surface of the release layer 501 of the release film 3. Specifically, the release film can be placed in an intermittent vacuum deposition device (EBH-800 manufactured by ULVAC), and a metal having a target thickness is placed on the deposition boat and then vacuumed until the vacuum reaches a degree of 9.0×10 -3 Pa or less, and then the evaporation boat is heated to perform vacuum evaporation. When the release layer is formed with a carbon layer, the release layer formation and the metal foil formation can be processed continuously without contact with the air between sputtering and evaporation.
[0103] (Method for producing electromagnetic wave shielding film)
[0104] Next, an example of a method for manufacturing an electromagnetic wave shielding film 2 is described. The electromagnetic wave shielding film has a protective film on the surface of the metal foil 301 of the metal foil with a release film 1 of the present invention, and has an adhesive layer on the surface on the opposite side. The method for manufacturing such an electromagnetic wave shielding film 2 is not particularly limited. For example, the following manufacturing method can be exemplified: after forming a protective film 602 on the surface of the metal foil 301 of the metal foil with a release film 1 of the present invention ( Figure 6 ), so that the release film is attached to the protective film 602 ( Figure 7 ), the release film 3 is peeled off, and after applying the adhesive layer composition on the release surface of the release film, the adhesive layer composition is cured to form an adhesive layer 601 ( Figure 8 ), and the adhesive layer is covered with a release film ( Fig. 9 ).
[0105] <Protective film forming process>
[0106] The protective film 602 is formed on the surface of the metal foil with a release film 1. The protective film 602 can be formed by laminating a product cured into a film-like shape, or by directly applying an uncured resin as a raw material of the protective film 602 on the surface of the metal foil with a release film 1, and then drying and heat-curing it.
[0107] As for the protective film 602, the method of laminating the product solidified into a film shape is not particularly limited, and may be roller lamination, stamping, etc. When the film-shaped protective film is laminated to the metal foil 301, the close fit of the protective film 602 and the metal foil 301 can be ensured by means of an adhesive. In the case of using an adhesive, the protective film 602 can be laminated after the adhesive is applied to the surface of the metal foil 301, or the adhesive can be applied to the metal foil 301 after being applied to the protective film 602 solidified into a film shape. At this time, a release film can be attached to the surface of the protective film 602. In addition, when an adhesive is not used, the protective film 602 can be formed into a film shape on the release film without completely curing the resin of the protective film 602, and the protective film 602 is overlapped with the release film and attached to the metal foil 301, and laminated. The uncured protective film 602 can be cured by heat treatment, etc. in the process after lamination, so as to have the function of a protective film.
[0108] There is no particular limitation on the method of applying the protective film 602 to the metal foil 301, and lip coating, comma coating, gravure coating, slot die coating, etc. can be used. Then, the protective film 602 is formed by heating and drying to remove the solvent or by curing the resin. A release film may be attached to the surface of the protective film 602.
[0109] <Adhesive layer forming step>
[0110] The timing of applying the adhesive layer composition to the surface of the metal foil 301 of the metal foil with a release film 1 of the present invention is preferably after the protective film 602 is formed. Since the adhesive layer 601 is used to bond and fix the flexible printed wiring board 4 to the electromagnetic wave shielding film 2, it is desirable to prevent the adhesion characteristics of the adhesive layer 601 from being deteriorated due to unnecessary heating steps, etc. after the adhesive layer 601 is formed until just before bonding with the flexible printed wiring board 4. It is further preferred that the adhesive layer forming step is the last step as much as possible in the process of forming the electromagnetic wave shielding film 2. After the protective film 602 is formed on the surface of the metal foil 301 of the metal foil with a release film 1 of the present invention, the release film 3 is peeled off, and the adhesive layer composition is applied to the surface of the metal foil 301 without the protective film 602 to form the adhesive layer 601. At this time, before peeling the release film 3, a release film can be bonded on the protective film 602 as a cover film. When the adhesive layer 601 is formed, the adhesive layer composition contains a resin composition and a solvent.
[0111] Solvents such as toluene, acetone, methyl ethyl ketone, methanol, ethanol, propanol, and dimethylformamide can be used. In addition, as required, the adhesive layer composition can also contain at least one of a curing accelerator, a tackifier, an antioxidant, a pigment, a dye, a plasticizer, an ultraviolet absorber, a defoamer, a leveling agent, a filler, a flame retardant, and a viscosity modifier. The ratio of the resin composition in the adhesive layer composition can be appropriately set according to the thickness of the adhesive layer 601, the coating method, the liquid viscosity, etc.
[0112] The method of applying the adhesive layer composition to the surface of the metal foil 301 on which the protective film 602 is not formed is not particularly limited, and lip coating, comma coating, gravure coating, slot die coating, or the like can be used.
[0113] Then, the adhesive layer composition is applied to the surface of the metal foil 301 in the present invention where the protective film 602 is not formed, and then heated and dried to remove the solvent, thereby forming the adhesive layer 601. A release film may be attached to the surface of the adhesive layer 601 as necessary.
[0114] (Shielded Printed Wiring Board)
[0115] The electromagnetic wave shielding film 2 can be used, for example, Fig.10 The shielded printed wiring board shown in FIG.
[0116] The printed wiring board includes a base layer 701, a printed circuit (ground circuit) 801 formed on the base layer 701, an insulating adhesive layer 901 provided on the base layer 701 adjacent to the printed circuit 801, and an insulating cover film 702 having an opening formed therein for exposing a portion of the printed circuit 801 and provided so as to cover the insulating adhesive layer 901. It should be noted that the insulating adhesive layer 901 and the cover film 702 constitute an insulating layer of the printed wiring board.
[0117] The base layer 701, the insulating adhesive layer 901 and the cover film 702 are not particularly limited, and may be, for example, a resin film, such as polypropylene, cross-linked polyethylene, polyester, polybenzimidazole, polyimide, polyamide-imide, polyetherimide, or polyphenylene sulfide. The printed circuit 801 may be, for example, a copper wiring pattern formed on the base layer 701.
[0118] It should be noted that the electromagnetic wave shielding film 2 is bonded to the printed wiring board with the adhesive layer 601 being located on the cover film 702 side.
[0119] Next, the manufacturing method of the shielded printed wiring board is described. The electromagnetic wave shielding film 2 is placed on the printed wiring board, and heated and pressed by a punching machine. A part of the adhesive layer 601 softened by heating flows into the opening formed on the cover film 702 due to the pressure. Thus, the metal foil 301 and the grounding circuit 801 of the printed wiring board are connected via the conductive adhesive, and the metal foil 301 is connected to the grounding circuit 801.
[0120] Example
[0121] Hereinafter, the present invention will be described based on examples. It should be noted that the present invention is not limited to these examples, and these examples can be deformed and changed based on the spirit of the present invention without excluding them from the scope of the invention.
[0122] (Magnetron Sputtering)
[0123] The film was placed in a batch vacuum deposition apparatus (EBH-800 manufactured by ULVAC) using a nickel target of 50 mm × 550 mm in size and the vacuum degree was adjusted to 5 × 10 -1 Pa or less, and continuously apply DC power for a certain period of time until the thickness of the metal foil reaches a predetermined value.
[0124] It should be noted that the vacuum deposition performed after sputtering is continuously processed without contact with the air between sputtering and deposition.
[0125] (Vacuum deposition)
[0126] The film was set in a batch vacuum deposition apparatus (EBH-800 manufactured by ULVAC), and copper having a target thickness was placed on a deposition boat and then vacuumed until the vacuum reached a degree of 9.0×10 -3 Pa or less, and then the evaporation boat is heated to perform vacuum evaporation.
[0127] (Measurement of surface roughness)
[0128] For surface roughness, a micro-shape measuring machine Surfcorder ET4000A manufactured by Kosaka Laboratory Co., Ltd. was used to fix the sample on a glass plate with a kamaboko shape, and a stylus with a tip R2μm was used. In addition, the three-dimensional surface roughness analysis system i-Face model TDA31 was used for data analysis. Data were randomly measured at 3 locations and collected, and their average values were taken as the values of Ra and Rz.
[0129] Measurement conditions: X measurement length 500μm, pitch 1μm
[0130] Y measurement length 500μm, pitch 5μm
[0131] The measuring speed is 0.1 mm / sec.
[0132] (Measurement of surface inclination)
[0133] The surface inclination was measured using a laser microscope VK-9700 manufactured by Keyence Corporation and analyzed using a shape analyzer VK-H1A1. The measurement was performed at three random locations, and the average values thereof were used as the values of RΔq and RΔa.
[0134] Measurement conditions: objective lens 50 times, zoom 1 times
[0135] Analysis conditions: Automatic denoising: Noise detection area Normal
[0136] Tilt correction: Surface tilt correction (automatic)
[0137] Line roughness analysis Analysis length 200μm
[0138] Height smoothing: Arithmetic mean ±2.
[0139] For the line roughness profile, cross-sectional data of 200 μm in length were collected at the center of each of the horizontal and vertical directions in the captured image, and the average of the two values was taken as RΔq and RΔa in the image.
[0140] (Measurement of surface resistance)
[0141] The surface resistance was measured by the 4-terminal method. The sample to be measured was cut into 100 mm squares, and the position of the cut film center was repeatedly measured three times, and the average value of the three times was taken as the measured value of the surface resistance. A simple low resistivity meter (Loresta EP MCP-T360 ASP probe manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was used for the measurement, and the unit was expressed as Ω / square.
[0142] (Method for measuring average crystal particle size)
[0143] The average crystal grain size of the metal foil is calculated using EBSD. First, a thin section of the metal foil of the stack is cut out to obtain its diffraction pattern. In the obtained diffraction pattern, the crystal particles are identified as the same particle if there are two or more measurement points within a specified azimuth angle difference of less than 5°. For each crystal grain, its equivalent circle diameter (the diameter of a circle of the same area) is calculated. The crystal grain sizes thus obtained are averaged according to the following formula, and the obtained value is taken as the average crystal grain size. In the formula, N represents the total number of particles, d i It represents the particle size (equivalent circle diameter) of each particle.
[0144] [Mathematical formula 2]
[0145]
[0146] It should be noted that the conditions for obtaining the diffraction pattern are as follows.
[0147] Device used:
[0148] Thermal field emission scanning electron microscope (TFE-SEM) JSM-6500F (manufactured by JEOL Ltd.)
[0149] OIM position analysis device DigiViewIV slow scan CCD camera
[0150] OIM Data Collection ver.7.x
[0151] OIM Analysis ver.7.x
[0152] Analysis conditions: Acceleration voltage 15 kV
[0153] Irradiation current 15nA
[0154] Sample tilt - 30 degrees (through EBSD method)
[0155] Surface measurement magnification 5,000 times
[0156] Measurement field of view: 3×20μm
[0157] The interval is 20 nm / step.
[0158] (Measurement of copper layer thickness)
[0159] The thickness of the metal layer was measured by a fluorescent X-ray film thickness meter (manufactured by SSI Nanotechnology, SFT9400).
[0160] (Water vapor transmission rate)
[0161] The water vapor permeability is measured using the method according to JIS K7129-2:2019 (infrared). The water vapor permeability measuring device (model name, "PERMATRAN (registered trademark)" W3 / 31) manufactured by MOCON Corporation of the United States was used for measurement at a temperature of 40°C and a humidity of 90% RH. In order to reduce the influence of oxidation on the metal surface, water vapor is passed through the release film side of the metal foil with a release film, and its permeability is measured. Two test pieces are measured twice each, and the average value of the total of four measured values is taken as the value of the water vapor permeability.
[0162] (Manufacture of electromagnetic wave shielding film)
[0163] An adhesive containing epoxy resin and spherical silver-coated copper powder (compounding amount 50 wt%) with an average particle size of 3 μm was applied on the surface of the metal foil of the metal foil with a release film to form an adhesive layer with a thickness of 5 μm.
[0164] (Manufacturing of shielded printed wiring boards)
[0165] The produced electromagnetic wave shielding film and printed wiring board were superimposed so that the adhesive layer of the electromagnetic wave shielding film and the printed wiring board faced each other, and heated and pressed for 1 minute at 170°C and 3.0 MPa using a punch press, and then heated and pressed for 3 minutes at the same temperature and pressure to produce a shielded printed wiring board.
[0166] It should be noted that the printed wiring board has: two copper foil patterns extending in parallel with each other with a spacing therebetween, and an insulating layer (thickness: 25 μm) formed of polyimide covering the copper foil patterns, and an opening (diameter: 1 mm) exposing each copper foil pattern is provided on the insulating layer. In addition, the adhesive layer of the electromagnetic wave shielding film is overlapped with the printed wiring board in such a manner that the opening is completely covered with the electromagnetic wave shielding film. After obtaining the shielded printed wiring board, the polyethylene terephthalate film subjected to the demolding treatment is peeled off.
[0167] (Reflow soldering performance)
[0168] The reflow resistance of the prepared shielded printed wiring board was evaluated in the following manner: As reflow conditions, a temperature profile was set such that the shielding film in the shielded printed wiring board was exposed to 265° C. for 1 second, assuming lead-free solder.
[0169] After the shielded printed wiring board was exposed to the temperature conditions of the above profile three times, it was visually confirmed whether interlayer adhesion was broken and swelling occurred. The case where swelling did not occur was rated as ○, and the case where swelling occurred was rated as ×.
[0170] (Evaluation of electric field shielding properties and magnetic field shielding properties)
[0171] The near electric field and near magnetic field shielding properties of the metal foil with release film were measured by the KEC method. The measuring equipment used was a microwave millimeter wave band evaluation system (E5071C ENA, network analyzer (9kHz to 4.5GHz) manufactured by Agilent) to measure the electric field shielding properties (near electric field shielding properties) and magnetic field shielding properties (near magnetic field shielding properties) at 1GHz.
[0172] (Example 1)
[0173] <Manufacturing of metal foil with release film>
[0174] One side of a biaxially oriented polyethylene terephthalate film ("Lumirror (registered trademark)" type: S10 manufactured by Toray Industries, Ltd.) having a thickness of 50 μm was subjected to shot peening at a distance of 1 m using silica sand having an average particle size of 200 μm as an abrasive material, and then washed with water to obtain a surface roughened film. The surface roughness of the film after surface roughening was Ra 0.87 μm, Rz 7.96 μm, and the inclination of the concave and convex was RΔq 0.56, RΔa 15.5°.
[0175] Next, carbon was deposited to a thickness of 3 nm on the surface with surface irregularities by magnetron sputtering. The conditions were that a DC power supply was used and the sputtering output power was set to 3.0 kW. Then, copper was vacuum deposited to a thickness of 2.0 μm by vacuum evaporation. The copper metal foil with a release film produced in this way had an average crystal grain size of 74 nm, a surface resistance of 0.0198 Ω / □, a surface roughness of Ra 1.05 μm, Rz 8.15 μm, and a slope of the irregularities of RΔq 0.70 and RΔa 16.3°. In addition, the water vapor permeability of the metal foil with a release film was 6.68 g / (m 2 · days), the electric field shielding property at 1 GHz was 80 dB, and the magnetic field shielding property at 1 GHz was 60 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ○.
[0176] (Example 2)
[0177] <Manufacturing of metal foil with release film>
[0178] A surface roughened film was prepared by coating a resin containing particles on a biaxially oriented polyethylene terephthalate film having a thickness of 50 μm (manufactured by Toray Industries, Inc., "Lumirror (registered trademark)" type: S10). The particle-containing resin used was a resin in which spherical silica particles "Seahostar" KE-P30 (average particle size of 0.3 μm) manufactured by Nippon Shokubai Co., Ltd. were dispersed in an acrylic resin "Acrydic (registered trademark)" WFL-908 manufactured by DIC Corporation in an amount of 15% by weight. The acrylic resin was coated with a Mayer bar and dried at 120°C for 1 minute to form a layer with a thickness of 0.5 μm, thereby obtaining a surface convex-concave film. The surface roughness of the obtained surface roughened film was Ra 0.51 μm, Rz 3.36 μm, and the inclination of the concave and convex was RΔq 0.21, RΔa 7.3°.
[0179] Next, carbon was deposited on the film surface to a thickness of 3 nm using magnetron sputtering. The conditions were that a DC power supply was used and the sputtering output power was set to 3.0 kW. Then, copper was vacuum deposited to a thickness of 1.0 μm using a vacuum evaporation method. The average crystal grain size of the copper metal foil with a release film produced in this way was 102 nm, and the surface resistance of the metal foil was 0.0280 Ω / □. The surface roughness of the metal foil was Ra 0.57 μm, Rz 4.92 μm, and the inclination of the concave and convex was RΔq 0.13, RΔa 4.6°. In addition, the water vapor permeability of the metal foil with a release film was 3.54 g / (m 2 ·day), the electric field shielding property at 1 GHz was 65 dB, and the magnetic field shielding property at 1 GHz was 51 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ○.
[0180] (Example 3)
[0181] <Manufacturing of metal foil with release film>
[0182] The metal foil with a release film was obtained under the same conditions as in Example 2 except that the copper was vacuum-deposited to a thickness of 0.7 μm by vacuum evaporation. The average crystal grain size of the copper metal foil with a release film produced in this manner was 106 nm, the surface resistance was 0.0384 Ω / □, the surface roughness of the metal foil was Ra 0.54 μm, Rz 4.28 μm, the inclination of the concave and convex was RΔq 0.18, and RΔa 6.1°. In addition, the water vapor permeability of the metal foil with a release film was 3.76 g / (m 2 ·day), the electric field shielding property at 1 GHz was 60 dB, and the magnetic field shielding property at 1 GHz was 49 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ○.
[0183] (Example 4)
[0184] <Manufacturing of metal foil with release film>
[0185] One side of a biaxially oriented polyethylene terephthalate film having a thickness of 50 μm (manufactured by Toray Industries, Inc., "Lumirror (registered trademark)" type: S10) was subjected to shot blasting and water washing to roughen the surface in the same manner as in Example 1. The surface roughness of the film after the surface roughening was Ra 0.87 μm, Rz 7.96 μm, and the inclination of the concavoconvex was RΔq 0.56, RΔa 15.5°.
[0186] Next, carbon was deposited on the film surface to a thickness of 3 nm using magnetron sputtering. The conditions were that a DC power supply was used and the sputtering output power was set to 3.0 kW. Next, a metal foil was formed on the film surface. The aforementioned film was set in an intermittent vacuum deposition apparatus (EBH-800 manufactured by ULVAC), and aluminum was placed on the deposition boat and vacuum was evacuated until the vacuum reached 9.0×10 -3 Pa or less, and then, the evaporation boat is heated to form a 2.0μm metal foil by vacuum evaporation. The average crystal grain size of the aluminum metal foil with a release film produced in this way is 91nm, and the surface resistance is 0.0379Ω / □. The surface roughness of the metal foil is Ra1.1μm, Rz 8.3μm, and the inclination of the concave and convex is RΔq 0.72, RΔa 16.5°. In addition, the water vapor permeability of the metal foil with a release film is 7.23g / (m 2 ·day), the electric field shielding property at 1 GHz was 60 dB, and the magnetic field shielding property at 1 GHz was 50 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ○.
[0187] (Comparative Example 1)
[0188] <Manufacturing of metal foil with release film>
[0189] With respect to the film surface, except that the roughening by shot peening was not performed, the metal foil with a release film was obtained under the same conditions as in Example 1. The surface roughness of the film before metal lamination was Ra 0.03μm, Rz 0.83μm, and the inclination of the concave and convex was RΔq 0.02, RΔa 0.69°. The average crystal grain size of the copper metal foil with a release film obtained by forming a metal foil on the surface of the film was 263nm, and the surface resistance was 0.0102Ω / □. The surface roughness of the metal foil was Ra 0.06μm, Rz 0.52μm, and the inclination of the concave and convex was RΔq 0.01, RΔa 0.41°. In addition, the water vapor permeability of the metal foil with a release film was 0.06g / (m 2 ·day), the electric field shielding property at 1 GHz was 86 dB, and the magnetic field shielding property at 1 GHz was 64 dB. The reflow soldering passability of the shielded printed wiring board made using the metal foil with a release film was ×.
[0190] (Comparative Example 2)
[0191] <Manufacturing of metal foil with release film>
[0192] The metal foil with a release film was obtained under the same conditions as in Comparative Example 1, except that a 1.5 μm metal foil was formed by copper vapor deposition. The surface roughness of the film before metal lamination was Ra 0.03 μm, Rz 0.83 μm, and the inclination of the concave and convex was RΔq 0.02, RΔa 0.69°. The average crystal grain size of the copper metal foil manufactured by forming a metal foil on the surface of the film to obtain a release film was 231 nm, and the surface resistance was 0.0133 Ω / □. The surface roughness of the metal foil was Ra 0.04 μm, Rz 0.62 μm, and the inclination of the concave and convex was RΔq 0.02, RΔa 0.52°. In addition, the water vapor permeability of the manufactured metal foil with a release film was 2.06 g / (m 2 ·day), the electric field shielding property at 1 GHz was 81 dB, and the magnetic field shielding property at 1 GHz was 60 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ×.
[0193] (Comparative Example 3)
[0194] <Manufacturing of metal foil with release film>
[0195] The metal foil with a release film was obtained under the same conditions as in Comparative Example 1, except that a 0.5 μm metal foil was formed by copper vapor deposition. The surface roughness before metal lamination was Ra 0.03 μm, Rz 0.83 μm, and the inclination of the concave and convex was RΔq 0.02, RΔa 0.69°. The average crystal grain size of the copper metal foil obtained by forming a metal foil on the surface of the film to obtain a release film was 227 nm, and the surface resistance was 0.0389 Ω / □. The surface roughness of the metal foil was Ra 0.04 μm, Rz 0.76 μm, and the inclination of the concave and convex was RΔq 0.02, RΔa 0.59°. In addition, the water vapor permeability of the metal foil with a release film was 2.93 g / (m 2 ·day), the electric field shielding property at 1 GHz was 60 dB, and the magnetic field shielding property at 1 GHz was 50 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ×.
[0196] (Comparative Example 4)
[0197] <Manufacturing of metal foil with release film>
[0198] With respect to the film surface, the manufactured metal foil with a release film was obtained under the same conditions as in Example 4, except that the roughening by shot peening was not performed. The surface roughness of the film before metal lamination was Ra 0.03μm, Rz 0.83μm, and the inclination of the concave and convex was RΔq 0.02, RΔa 0.69°. The average crystal grain size of the manufactured aluminum metal foil with a release film obtained by forming a metal foil on the film surface was 272nm, and the surface resistance was 0.0371Ω / □. The surface roughness of the metal foil was Ra 0.05μm, Rz 0.61μm, and the inclination of the concave and convex was RΔq 0.01, RΔa 0.56°. In addition, the water vapor permeability of the manufactured metal foil with a release film was 0.03g / (m 2 ·day), the electric field shielding property at 1 GHz was 60 dB, and the magnetic field shielding property at 1 GHz was 50 dB. The reflow soldering passability of the shielded printed wiring board produced using the metal foil with a release film was ×.
[0199] [Table 1-1]
[0200]
[0201] [Table 1-2]
[0202]
[0203] Description of Reference Numerals
[0204] 1 Metal foil with release film
[0205] 2 Electromagnetic wave shielding film
[0206] 3 Release film
[0207] 4 Flexible printed wiring board (printed wiring board)
[0208] 5 Shielded printed wiring board
[0209] 101, 102, 103, 104 membrane
[0210] 201 Evaporation direction
[0211] 301 metal foil
[0212] 401 Evaporated film growth direction
[0213] 501, 502, 503 release layer
[0214] 601 Adhesive layer
[0215] 602 protective film
[0216] 701 Base layer
[0217] 702 Covering Film
[0218] 801 Printed circuit (grounding circuit)
[0219] 901 Insulating adhesive layer
Claims
1. A metal foil with a release film, which comprises a release layer and a metal foil in this order on one side of the film, wherein the surface resistance of the metal foil is 0.04 Ω / □ or less, and the water vapor transmission rate of the metal foil with a release film according to JIS K7129-2:2019 is 3.5 g / (m 2 · days) or more.
2. The metal foil with a release film according to claim 1, wherein The surface resistance of the metal foil is 0.02Ω / □ or less.
3. The metal foil with a release film according to claim 1, wherein The root mean square inclination RΔq of the film surface on the side having the metal foil is 0.18 or more.
4. The metal foil with a release film according to claim 1, wherein The arithmetic mean inclination angle RΔa of the film surface on the side having the metal foil is 7.0° or more.
5. The metal foil with a release film according to claim 1, wherein The arithmetic mean roughness Ra of the film surface on the side having the metal foil is 0.4 μm or more.
6. The metal foil with a release film according to claim 1, wherein The ten-point average roughness Rz of the film surface on the side having the metal foil is 2.5 μm or more.
7. The metal foil with a release film according to claim 1, wherein The metal foil has an average crystal grain size of 50 nm or more and 200 nm or less.
8. The metal foil with a release film according to claim 1, wherein The main component of the metal foil is at least one metal selected from the group consisting of copper, silver, and aluminum.
9. The metal foil with a release film according to claim 1, wherein The thickness of the metal foil is not less than 0.5 μm and not more than 3.0 μm.
10. The metal foil with a release film according to claim 1, wherein The arithmetic mean square root inclination RΔq of the metal foil surface is 0.10 or more.
11. The metal foil with a release film according to claim 1, wherein The arithmetic mean inclination angle RΔa of the metal foil surface is 3.0° or more.
12. The metal foil with a release film according to claim 1, wherein The metal foil surface has an arithmetic mean roughness Ra of 0.5 μm or more.
13. The metal foil with a release film according to claim 1, wherein The ten-point average roughness Rz of the metal foil surface is 3.5 μm or more.
14. The metal foil with a release film according to claim 1, wherein The film includes at least one resin selected from the group consisting of polyester, polyimide, polyphenylene sulfide, polypropylene, polyetheretherketone, and epoxy resin.
15. The metal foil with a release film according to claim 1, wherein The metal foil has a rust-proof layer on the side opposite to the film side.
16. The metal foil with a release film according to claim 15, wherein The rust-proof layer is a metal layer including at least one selected from the group consisting of nickel, titanium, and chromium.
17. The metal foil with a release film according to claim 15, wherein The thickness of the anti-rust layer is greater than or equal to 2 nm and less than or equal to 30 nm.
18. A method for producing a metal foil with a release film, which is the method for producing a metal foil with a release film according to claim 1, wherein: The metal foil is formed into a film by vacuum deposition.
19. A method for producing a metal foil with a release film, which is the method for producing a metal foil with a release film according to claim 15, wherein: The rust-proof layer is formed by sputtering, and the metal foil is formed by vacuum deposition.
20. The method for producing a metal foil with a release film according to claim 18, wherein: The metal foil is formed into a film by oblique vapor deposition.
21. The method for producing a metal foil with a release film according to claim 20, wherein: Concavities and convexities are formed on the surface of the film.
22. A method for producing an electromagnetic wave shielding film, wherein: An adhesive layer is formed on one side of the metal foil peeled off from the metal foil with a release film according to claim 1, and a protective film is formed on the side of the metal foil opposite to the side on which the adhesive is formed.
Citation Information
Patent Citations
Bolt delivery device
JP1987019383A
Electromagnetic wave shielding film and method for manufacturing same
WO2017111158A1
Metallized film and manufacturing method therefor
WO2020203109A1
Metallized film and manufacturing method therefor
CN113631370A
Shielding film for printed wiring board and its manufacturing method
JP2005276873A